2019
DOI: 10.1007/s12055-019-00869-0
|View full text |Cite
|
Sign up to set email alerts
|

Graft patency at 3 months after off- and on-pump coronary bypass surgery: a randomized trial

Abstract: Purpose Coronary artery bypass grafting (CABG) is performed either with the aid of cardiopulmonary bypass (on-pump) or without cardiopulmonary bypass (off-pump). There is a scarcity of angiographic data to support the non-inferiority of off-pump technique to on-pump technique. The objective of this study is to ascertain the non-inferiority of off-pump CABG when compared to on-pump CABG in terms of angiographically assessed graft patency at 3 months. Methods A total of 320 patients with multivessel coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…12 Similar to the current study, a multicentric randomised trial on 320 patients found that off-pump CABG was not inferior to on-pump CABG in terms of 3-month post-operative graft patency. 13 A study reported that off-pump CABG had a beneficial effect in terms of AKI. 14 The current study found 1 case of AKI in the on-pump group and no cases of AKI in the off-pump group, but this was not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…12 Similar to the current study, a multicentric randomised trial on 320 patients found that off-pump CABG was not inferior to on-pump CABG in terms of 3-month post-operative graft patency. 13 A study reported that off-pump CABG had a beneficial effect in terms of AKI. 14 The current study found 1 case of AKI in the on-pump group and no cases of AKI in the off-pump group, but this was not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…We reported the graft patency outcomes and early clinical outcomes of the Prospective Randomized comparison of Off-pump and On-pump Multivessel coronary artery bypass surgery To Evaluate outcomes and graft patency (PROMOTE patency) trial previously. 6,7 The aim of the current study is to assess the 5-year clinical outcomes of OPCAB and ONCAB techniques in a post hoc analysis of the PROMOTE patency trial.…”
Section: Introductionmentioning
confidence: 99%
“…Some articles have reported that there was no difference in survival after off-pump versus on-pump or conventional CABG (22)(23)(24). Several recent articles have reported that there was no difference in patency between off-pump and on-pump CABG (25,26). However, it is doubtful whether it is appropriate to differentiate CABG into off-pump versus on-pump in evaluating graft patency, as on-pump beating CABG is technically similar to offpump CABG.…”
mentioning
confidence: 99%